(untitled) (Journal of Universal Science Research, 2025)
The problem of noise removal and restoration from digital images is relevant in computer vision, medical diagnostics, artificial intelligence systems, and many other fields. The introduction of various noises into an image, such as salt-and-pepper or Gaussian noise, degrades the image quality and complicates its analysis. This article analyzes the process of image denoising and restoration based on mathematical modeling. In particular, the application of fuzzy set theory to this problem is discussed.